KONSEP DAN IMPLIKASI MAKNA MENGAJAR DALAM PERPEKTIF DOSEN - Abu Amar (Cendekia, 2019)
This study attemps to observe the meaning of instruction according to the lectures at STIT Al-Fattah - Lamongan. Using qualitative approach, this case study presents a natural and objective illustration of the problem. The data accurately and carefully analyzed based on inductive – qualitative analysis. The analysis come up with conclution that: the meaning of instruction according to the perception of the lectures at STIT Al-Fattah - Lamongan is the activity interconnected with transfer of knowledge, transfer of value, and transfer of skill. This activity has competention as a purpose that will be given to the students appropriate to the subjects that lectures teach them in the form ability to think, ability to have a certain attitude, and ability to act. With the abilities we expect the students can solve the problem that they face in the sociaty. The implication of the perception about the instruction in the instructional activity of the lectures can be seen at follows: in the instructional activity the lectures begin with making syllabus of the subject then followed by contruct the course outline that have contents; instructional objective, time line, instructional strategy, and the evaluation. In the instructional activity the lecture must play as a motivator, mediator, fasilitator, and dinamisator to the students in order they have a high motivation in study.